Faktor Risiko Lingkungan Yang Berhubungan Dengan Kejadian Pneumonia Pada Balita (Studi di Wilayah Kerja Kerja Dinas Kesehatan Kota Bengkulu) - Suryani, Suryani; Hadisaputro, Suharyo; Zain, Sidartani (HIGIENE: Jurnal Kesehatan Lingkungan, 2018)
Pneumonia is a major cause of morbidity and mortality of infectious diseases in the world. In 2010 the incidence of pneumonia in Bengkulu was 5 per 1000 children under 5 years old and in 2011 the incidence increased to 6 per 1000 children under 5 years old. The objective of the study was to analyze the correlation of environmental risk factors related to the incidence of pneumonia in children. The design was a case-control study and indepth interview done in Sukamerindu health center, Jembatan Kecil health center, Beringin Raya health center, and Lingkar Barat health center. The subjects were pneumonia patients that came for treatment in January 2011 – April 2012 and the respondent house had not experienced an improvement over the last 1 year. Multivariate analysis using multiple logistic regression (confidence interval (CI) of 95% and a = 0,05) was done. The number cases was 67, control was 67, total sample was 134 .The risk factor for pneumonia was ventilation (p: 0.000; OR: 5.99, 95% CI: 5.52 to 14.23), overcrowding (p: 0.018; OR: 2.94, 95% CI: 1.207 to 7.191), and smokers in the household (p: 0.021; OR: 2.76, 95% CI: 1.162 to 6.579). The variables that proved to be risk factors for the incidence of pneumonia in children are: ventilation, overcrowding, smokers in the household. Keywords : Pneumonia, Children Under 5 Years Old, Environmental Risk Factors.